School Culture: Approaching a Complex Concept - María Esther Elías (Revista Electrónica Educare)
Studies about school culture have made important contributions to understand what happens inside the school. Nevertheless, the way in which school culture is conceptualized varies significantly. Through a literature review from the 70s to the present day, this paper explores the different meanings adopted by the concept of school culture in the educational field. This paper is organized in four sections, and it begins with a description of the most common ways of defining school culture. This is followed by a review of the theoretical and methodological perspectives in which the concept is framed and used. Thirdly, the ways of organizing information on school culture used by researchers working from different theoretical perspectives are presented. Finally, two related concepts –school climate and school grammar, are reconsidered and compared to school culture. The information presented shows the different approaches used in studying school culture and the frequent overlapping with the concepts of school environment and school grammar. However, the ambiguity in the definition gives the concept of school culture a great theoretical potential by providing multiple tools to understand what happens inside schools.